EFEKTIVITAS MODEL PBL BERBANTUAN MEDIA TEKON UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS REKON SISWA KELAS IV - Septi Ayu Widia Ningrum -; Kustina Puji Astuti; Zumroh Kusuma Darmasari; Qurrotu A'yunina Fais; Rani Setiawaty (FKIP Universitas Wiraraja, 2026)
The ability of fourth-grade students at SDN 1 Megawon to write narrative texts remains relatively low, as evidenced by the fact that 63.2% of students scored below the minimum passing score (KKM), with a class average of 71.5. This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model assisted by Tekon media in improving the narrative writing skills of fourth-grade students at SDN 1 Megawon. The study employed a quantitative approach using a One-Group Pretest-Posttest Design. The research subjects were 19 fourth-grade students at SDN 1 Megawon, selected using a saturated sampling technique. The instrument used was a narrative text writing assessment rubric with seven indicators. Data analysis included the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain test. The results showed that the pre-test average of 72.47 increased to 86.47 on the post-test. The Paired Sample t-Test results indicated a significance value of 0.000 < 0.05, indicating a significant difference before and after the intervention. The N-Gain value of 0.48 falls into the moderate category (fairly effective). Thus, the PBL model supported by the Tekon media is quite effective in improving the text reconstruction writing skills of fourth-grade students at SDN 1 Megawon optimally and sustainably.